Inculcating financial literacy among young adults through trust and experience - Abdul Hayei, Afaf; Khalid, Haniza (Academic Inspired Network, 2019)
The current and future financial choices of the young generation are likely to be more challenging than those of their parents, given the greater complexity in financial products, use of new digital technology, new financial systems and regulations. Thus, this study attempts to measure the financial literacy (FL) amongst a specific group of students i.e. upper-secondary students of a private religious school. It is expected that parents’ educational achievement, occupational and income levels of this group to be almost invariable, therefore allowing us to focus on other factors that influence financial literacy. FL is measured using two latent constructs namely, financial knowledge and financial behaviour, covering aspects such as general money management, investment management, credit management, charity giving and entrepreneurship. The findings of this study show that while their level of financial knowledge is generally good, the majority of respondents are not entrusted nor guided to manage their own finances, make budgets and record their expenditures; particularly since most schooling expenses including food and transport are paid in advance by their parents. Around 85.2 percent reported zero or very little experience in business or helping out in business activities at school or for their family members. Parents and the school authorities must realize that financial literacy is worth investing time and resources into if the future generation is to lead financially sustainable lives. Policymakers need to design effective interventions targeted at this age group, aiming towards empowering individuals to manage their financial matters effectively and towards promoting responsible consumer behaviour.